2017
DOI: 10.1063/1.4995811
|View full text |Cite
|
Sign up to set email alerts
|

Development of high sensitivity 4H–SiC detectors for fission neutron pulse shape measurements

Abstract: 4H-silicon carbide (4H-SiC) detectors are well suited for measurements of fission neutron pulse shape for their compact size, excellent radiation resistance, and hydrogen free composition. The aim of this study is to improve the 4H-SiC detector's sensitivity to fission neutron pulses. 4H-SiC detectors with varied epilayer thicknesses are fabricated and then tested in the pulsed neutron field of the Chinese Fast Burst Reactor II (CFBR II). The sensitivity of the 4H-SiC detector to the CFBR II neutron pulse is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…1,2 Due to its wide band gap, radiation hardness, high breakdown field and melting point, SiC is also a promising semiconductor for the fabrication of nuclear radiation detectors working in harsh environments, including at high temperature and dense radiation fields. [3][4][5] SiC-based diodes for radiation detection are highly sensitive to defects that introduce deep carrier traps, 3 especially to those with large capture cross section for minority carriers which hold the actual impact signal. Point defects in SiC are mainly created during i) semiconductor material growth, ii) device processing by ion-implantation or iii) during operation under radiation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Due to its wide band gap, radiation hardness, high breakdown field and melting point, SiC is also a promising semiconductor for the fabrication of nuclear radiation detectors working in harsh environments, including at high temperature and dense radiation fields. [3][4][5] SiC-based diodes for radiation detection are highly sensitive to defects that introduce deep carrier traps, 3 especially to those with large capture cross section for minority carriers which hold the actual impact signal. Point defects in SiC are mainly created during i) semiconductor material growth, ii) device processing by ion-implantation or iii) during operation under radiation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [108] investigated the performance of 4H-SiC detectors for fission neutron measurements. They demonstrated that increasing the thickness of the epitaxial layer from 20 to 120 μm improves sensitivity to neutron pulses by 139.8%.…”
Section: Fission Neutronsmentioning
confidence: 99%
“…As is well-known, the energy spectrum and number of neut-rons produced by fusion reactions can be used to characterize the temperature and the total amount of reaction products [14,15]. The pulsed neutron flux [16], energy spectrum [17,18] and time structure [19,20] are the most important parameters in measuring a pulsed neutron process.…”
Section: Introductionmentioning
confidence: 99%